Self-assembly of chlorophenols in water - Rogalska, Ewa (The National Academy of Sciences, 1999)
In saturated solutions of some di- and trichlorophenols, structures with complex morphologies, consisting of thin, transparent sheets often coiling into helices and ultimately twisting into filaments, were observed under the optical microscope. Freeze-fracture electron microscopy, x-ray diffraction, phase diagrams, and molecular modeling were performed to elucidate the observed phenomena. Here, we present evidence that the chlorophenols studied, when interacting with water, self-assemble into bilayers. The fact that some chlorophenols form the same supramolecular structures as those described previously for structurally nonrelated surfactants sheds light on the mechanisms of self-assembly.